2015
DOI: 10.1186/s40199-015-0111-z
|View full text |Cite
|
Sign up to set email alerts
|

A study on quantitative structure–activity relationship and molecular docking of metalloproteinase inhibitors based on L-tyrosine scaffold

Abstract: BackgroundMMP-2 enzyme is a kind of matrix metalloproteinases that digests the denatured collagens and gelatins. It is highly involved in the process of tumor invasion and has been considered as a promising target for cancer therapy. The structural requirements of an MMP-2 inhibitor are: (1) a functional group that binds the zinc ion, and (2) a functional group which interacts with the enzyme backbone and the side chains which undergo effective interactions with the enzyme subsites.MethodsIn the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Computational studies have revealed their importance in understanding of biological systems through reliable tools. , The advent of computer speed and capacity took scientists to the level of extracting intricate details through multiscale simulation of biomolecules . To obtain new inhibitors, molecular docking and MD simulations are important techniques to have an insight into mechanisms of macromolecules and to conduct inexpensive investigations against databases. In recent studies, fascinating work reported against Hsp90 inhibition mechanism through 3D-QSAR approach by building a pharmacophore model of hydrogen bond acceptor, hydrogen bond donor and hydrophobic groups against Hsp90 inhibitors. These studies are performed on different training data sets of compounds and provided the most suitable pharmacophore features which are essential for the Hsp90 binding mechanism. Meanwhile, in-silico pipelines are applied via structure/ligand-based drug design which considers a binding site favored orientation conformation and estimates the stability of protein–ligand interactions to develop a new drug molecule. , Docking methods build a stable complex via offering preferred orientations and energies of a ligand with the active site of a receptor molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies have revealed their importance in understanding of biological systems through reliable tools. , The advent of computer speed and capacity took scientists to the level of extracting intricate details through multiscale simulation of biomolecules . To obtain new inhibitors, molecular docking and MD simulations are important techniques to have an insight into mechanisms of macromolecules and to conduct inexpensive investigations against databases. In recent studies, fascinating work reported against Hsp90 inhibition mechanism through 3D-QSAR approach by building a pharmacophore model of hydrogen bond acceptor, hydrogen bond donor and hydrophobic groups against Hsp90 inhibitors. These studies are performed on different training data sets of compounds and provided the most suitable pharmacophore features which are essential for the Hsp90 binding mechanism. Meanwhile, in-silico pipelines are applied via structure/ligand-based drug design which considers a binding site favored orientation conformation and estimates the stability of protein–ligand interactions to develop a new drug molecule. , Docking methods build a stable complex via offering preferred orientations and energies of a ligand with the active site of a receptor molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3,7,47 ] The ability of peptides to bind to different receptors and be a part of various biochemical pathways allows them to function as potential diagnostic tools and biomarkers. [ 48–55 ]…”
Section: Resultsmentioning
confidence: 99%
“…Apart from that, various ligand-based and structure-based drug design strategies (such as 2D-QSAR; HQSAR; classification-based QSAR through linear discriminant analysis, recursive partitioning, and Bayesian classification; machine learning approaches such as support vector machine (SVM), k -nearest neighbor ( k -NN), decision tree (DT), and random forest (RF); 3D-QSAR pharmacophore mapping; CoMFA, CoMSIA, and topomer CoMFA; 4D-QSAR; molecular docking and MD simulation) have already been carried out by various groups of researchers to accelerate the design and discovery of potential MMPIs targeting the medium-size S1′ pockets for the management of several disease conditions (Table S2). ,, …”
Section: Selective Inhibitors Of Mmps Containing Intermediate S1′ Poc...mentioning
confidence: 99%
“…4 These MMPs are grouped into six different classes based on their substrate specificity, i.e., (i) collagenases development of tumors and the invasion of inflammatory cells. 5 As far as the MMPIs are concerned, many of the firstgeneration MMPIs were generally nonselective but some MMPIs exhibited selectivity toward a particular MMP having affinities against others. On the basis of the experimental and clinical evidence associated with MMPs regarding tumor progression and poor prognosis, several MMPIs were designed, synthesized, and evaluated in clinical trials from the late 1980s up to the early 2000s for the management of various types of cancers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation